Textural And Rheological Properties Of Gelatin Or Gellan In Maize Starch – Egg White Composite Gels - Foo, Wan Teck (2013)
Gellan (Gll) has been suggested as one of the gelatin (Glt) alternatives as the Gll gels could provide ‘melt-in-mouth’ sensory perception that is similar to Glt gels. However, the application of Gll as a Glt replacer in composite systems has not been sufficiently explored. The purpose of this study was to elucidate the effects of ingredient proportions on the texture, rheology and structural properties of Glt or Gll composite gels consisted of maize starch (MS) and egg white (EW). These main ingredients were chosen to yield gels based on their practical importance in the food industry. Mixture design experiment was applied as a tool in exploring the interaction effects of different proportions of the components. Textural properties and breakdown behaviour of single component gels were determined by using texture profile analysis (TPA) and multiple extrusion cell analysis (MEC), respectively. Rheological properties of composite gels under compression were determined by using stress relaxation test (linear deformation) and fracture analysis. The structural properties of gels were revealed through the gel formations that were determined by using rheometer. The morphologies of selected gels obtained from scanning electron microscopy images further revealed the structures of gels. The relationships of structure, rheology and texture of the gels were then assessed and compared between Glt and Gll systems. From TPA results, Glt gel was strong and elastic while Gll gel was weak and brittle. However, Glt and Gll gels showed similar decay patterns and rates in MEC test. This tentatively supports the notion of Gll as a Glt replacer in food products.